A Case of Epidermal Cyst with Underlying Lipoma on the Back: A Rare Presentation - Yuichi Kurihara; Koji Kawamura; Masutaka Furue (Karger Publishers, 2021)
The coexistence of epidermal cysts and lipomas at the same site is extremely rare, although epidermal cysts and lipomas are both common benign skin tumors. We present a rare case of an epidermal cyst with underlying lipoma on the back. This case report may simply be a result of coincidence, but the possibility of underlying subcutaneous tumors should be considered before epidermal cyst surgery.